2010
DOI: 10.1158/1078-0432.ccr-09-0957
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP2 and IGFBP3 Protein Expressions in Human Breast Cancer: Association with Hormonal Factors and Obesity

Abstract: Purpose: The insulin-like growth factor (IGF) signaling system is involved in breast cancer initiation and progression. The prognostic relevance of tumor expression patterns of IGFI-related proteins remains poorly understood. This study associates the expression of selected IGF proteins with breast tumor and patient characteristics.Experimental Design: IGFI, IGFI receptor, IGF-binding protein (IGFBP)2, and IGFBP3 expression was measured in 855 primary breast carcinomas by immunohistochemistry using tissue micr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 47 publications
3
52
0
Order By: Relevance
“…These proteins were selected based on the interest for the indirect detection of the administration of growth hormone in anti-doping analysis [17][18][19] and in relation to growth disorders, or as potential biomarkers of interest for cancer disease [20][21][22][23][24]. The fact that these proteins had a medium and low abundance and the necessity for short and high-throughput analysis made necessary to apply a first sample preparation step to reduce sample complexity and increase the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins were selected based on the interest for the indirect detection of the administration of growth hormone in anti-doping analysis [17][18][19] and in relation to growth disorders, or as potential biomarkers of interest for cancer disease [20][21][22][23][24]. The fact that these proteins had a medium and low abundance and the necessity for short and high-throughput analysis made necessary to apply a first sample preparation step to reduce sample complexity and increase the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…We employed the optimised precipitation protocol to develop a method for targeting the low mass proteins IGF1 (7.6 kDa), IGF2 (7.5 kDa), IBP2 (31.5 kDa), IBP3 (28.7 kDa) and A2GL (34.3 kDa), all of them putative or confirmed protein biomarkers of medium and low abundance, selected based on their relevance within the anti-doping [17][18][19] and clinical analysis [20][21][22][23][24]. Plasma samples were precipitated at 60% ACN and 30-fold diluted plasma (i.e., at a plasma protein concentration of~2 g/L) and quantified by SRM LC-MS/MS experiments, which is the method of choice for targeted and quantitative protein analysis [43], based on proteotypic tryptic peptides derived from plasma protein digests (Table 1).…”
Section: Srm Lc-ms/ms Analysis Of Igf1 Igf2 Ibp2 Ibp3 and A2gl Promentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studies from a number of groups have demonstrated growthpromoting activity of IGFBP-3 in vitro (7)(8)(9)(10)(11) and elevated gene expression of IGFBP3 occurs in a range of malignancies (12)(13)(14). In human breast tumors, expression of IGFBP-3 is correlated with markers of poor prognosis such as ER and PR negativity, S-phase fraction, and tumor size (15)(16)(17)(18). These clinical observations were recapitulated in a xenograft tumor model in which T47D cells expressing IGFBP-3 as a result of cDNA transfection developed larger tumors than control cells in nude mice (19).…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism by which breast cancer cells escape tamoxifeninduced apoptosis may be the activation of the AKT pathway via IGF-mediated signaling, which leads to phosphorylation of ER at serine 167 (Ser-167) and subsequent ligand-independent activation of ER (12). Additionally, IGF-binding protein 2 (IGFBP-2) mRNA and protein levels have been reported to be augmented in cell lines resistant to the antiestrogens fulvestrant and tamoxifen (13). Selective targeting agents are being investigated in combination with endocrine therapy, in an attempt to overcome or prevent endocrine resistance in breast cancer therapeutics.…”
Section: Rewiring Transcription Factor Network In Breast Tumorsmentioning
confidence: 99%